100 The prevalence of indicators of relative energy deficiency in sport (RED-S) in Australian elite and pre-elite female athletes. (3rd March 2020) - Rogers, Margot; Vlahovich, Nicole; Hughes, David; Pyne, David; Halson, Shona; Lovell, Gregory; Appaneal, Renee; West, Nic; Lundy, Bronwen; Welvaert, Marijke; Burke, Louise; Waddington, Gordon; et al.
Abstract : Background: Athlete health, training availability and performance can be impeded due to Relative Energy Deficiency in Sport (RED-S). Development of RED-S is underpinned by low energy availability (LEA), however its natural history is yet to be defined. Objective: To quantify the prevalence of issues previously described in association with RED-S in a mixed-sport cohort of female athletes, to inform the definition of its natural history. Design: This cross-sectional, observational study in athletes from eight sports utilised validated screening questionnaires and clinical investigations. Setting: Athletes were competing and/or training at a state, national or international level at the time of recruitment. Questionnaire data were collected electronically, whilst clinical investigations were undertaken at the Australian Institute of Sport. Participants: Females ≥15 years old from the National Sporting Organisations approached by the researchers were eligible (n=112). Assessment of risk factors: Psychology, nutrition and sleep screening questionnaires were administered. Fasted blood tests, indirect calorimetry, dual-energy x-ray absorptiometry scans, and diagnostic psychiatric clinical interviews were undertaken. Main outcome measurements: Menstrual function, bone mineral density, thyroid function, resting metabolic rate, serum ferritin, mental health, lipid profile, gastrointestinal symptoms and recent illness and/or injury resulting in sports incapacity were assessed as indicators of the health consequences associated with RED-S. Results: Almost all (87%) participants demonstrated at least one indicator of RED-S consequences, with 81% exhibiting between one and three indicators. Participants most commonly displayed impairments of the immunological (24%), cardiovascular (28%), haematological (29%) and gastrointestinal (46%) systems. Risk of LEA was identified in 11–55% of participants, and one third of the assessed cohort had a diagnosed psychiatric condition. Conclusions: RED-S consequences were prevalent. These results have informed secondary prevention strategies whereby early detection of symptoms leads to early intervention prior to multi-system involvement. Further work is warranted to determine the interactions between these impairments, LEA and subsequent RED-S, to inform treatment and prevention.